Conservation and preservation: interactions between theory and practice ; in memoriam Alois Riegl (1858 - 1905) ; proceedings of the International Conference of the ICOMOS International Scientific Committee for the Theory and the Philosophy of Conservation and Restoration, 23 - 27 April 2008 (Vienna, Austria) - Falser, Michael; Lipp, Wilfried (Edizioni Polistampa, 2010)
After the first conference of the ISC Theory in Florence 2007, Values and Criteria in Heritage Preservation, the Vienna Conference in 2008 was planned as a commemoration of the 150th birth anniversary of Alois Riegl. The volume honours his work with contributions of: Wilfried Lipp, Michael S. Falser, Paolo Del Bianco, Niels Gutschow, Jukka Jokilehto, Christiane Schmuckle-Mollard, Peter Burman, Andreas Lehne, Ursula Schädler-Saub, Bogusl aw Szmygin, Andrzej Tomaszewski, Duncan Marshall, Zbigniew Kobylinski, Christoph Machat, Irmela Spelsberg, Natalia Dushkina, Erzsébet Kovács, Jörg Haspel, Gamini Wijesuriya, Giora Solar, Dinu Bumbaru, Eduard Sekler
El. ed. at: http: / / digital.casalini.it/ 9788859607465
Literaturang
Incl. 1 text in English and German. - Cont. bibl. refs. and notes. - Proceedings. - Festschrift Alois Riegl
Keywords: Konferenzschrift -- 2008 -- Wien; Festschrift; Kunstwissenschaft; Kunst; Konservierung; Kulturerbe; Denkmalschutz; Restaurierung